Local-Activity and Simultaneous Zero-Hopf Bifurcations Leading to Multistability in a Memristive Circuit - Messias, Marcelo [UNESP]; Reinol, Alisson De Carvalho (World Scientific Publishing, 2021)
In this paper, we consider a memristive circuit consisting of three elements: A passive linear inductor, a passive linear capacitor and an active memristive device. The circuit is described by a four-parameter system of ordinary differential equations. We study in detail the role of parameters in the dynamics of the system. Using the existence of first integrals, we show that the circuit may present a continuum of stable periodic orbits, which arise due to the occurrence of infinitely many simultaneous zero-Hopf bifurcations on a line of equilibria located in the region where the memristance is negative and, consequently, the memristive device is locally-Active. These bifurcations lead to multistability, which is a difficult and interesting problem in applied models, since the final state of a solution depends crucially on its initial condition. We also study the control of multistability by varying a parameter related to the state variable of the memristive device. All analytical results obtained were corroborated by numerical simulations.
Keywords: first integral; invariant algebraic surface; local-Activity; memristive circuit; Memristive device; multistability; periodic oscillation; zero-Hopf bifurcation